2014
DOI: 10.1097/inf.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based National Bacterial Meningitis Surveillance in Turkey

Abstract: Polymerase chain reaction-based surveillance for bacterial meningitis including 841 children revealed 246 with bacterial DNA in cerebrospinal fluid samples of which 53% were Streptococcus pneumoniae, 19% Neisseria meningitidis, and 16% Haemophilus influenzae type b. The most common S. pneumoniae serotypes/serogroups were 1, 19F, 6A/6B, 23F, 5, 14, 18 and 19A. Among 47 meningococci, 86% were serogroup B, 6% serogroup C, 3% serogroup A, 3% serogroup X and 3% serogroup W.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 11 publications
0
24
0
4
Order By: Relevance
“…The pneumococcal isolates were serotyped using the Centers for Disease Control and Prevention (CDC) procedure, and the multiplex PCR reactions were performed according to a published protocol [6,7]. For the eight different multiplex PCR reactions, 40 primer pairs were used to detect the serotypes, as follows: 1, 2, 3, 4, 5, The multiplex PCR reactions were performed using an iCyclerTermal Cycler (Biorad) under the following conditions: 94°C for 4 min of initial denaturation, 30 cycles at 94°C for 45 s, 54°C for 45 s, and 65°C for 2 min and 30 s (see http://www.…”
Section: Multiplex Pcr Reactions For Serotypingmentioning
confidence: 99%
“…The pneumococcal isolates were serotyped using the Centers for Disease Control and Prevention (CDC) procedure, and the multiplex PCR reactions were performed according to a published protocol [6,7]. For the eight different multiplex PCR reactions, 40 primer pairs were used to detect the serotypes, as follows: 1, 2, 3, 4, 5, The multiplex PCR reactions were performed using an iCyclerTermal Cycler (Biorad) under the following conditions: 94°C for 4 min of initial denaturation, 30 cycles at 94°C for 45 s, 54°C for 45 s, and 65°C for 2 min and 30 s (see http://www.…”
Section: Multiplex Pcr Reactions For Serotypingmentioning
confidence: 99%
“…‡ References [16,18,19,22] are particularly important studies because of their prospective design, sample size, representativeness and molecular methods used for diagnosis like PCR. § Ratio of deaths associated with meningitis and complications regardless of the involved etiological agent for all cases.…”
mentioning
confidence: 99%
“…Previous studies investigating invasive meningococcal diseases reported serogroup B as the leading serogroup, especially in European countries and Turkey, in recent years [4,18]. Another study from Turkey reported that serogroup B was the most common cause of meningococcal meningitis in the Marmara region, including the city of Istanbul [5].…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, the meningococcal vaccines are not implemented in the NIP but are recommended for highrisk groups including Hajj pilgrims and military recruits. Moreover, few surveillance data exist on meningococcal invasive diseases in Turkey [4,5]. During the years 2006 to 2009, we performed national bacterial meningitis surveillance in children and found that N. meningitidis was the second-most common pathogen, and after 2008, due to implementation of Haemophilus influenzae type b vaccine and pneumococcal conjugated vaccine in NIP, N. meningitidis became the leading pathogen in 2008 and 2009 [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation